MANAGEMENT HUMAN RESOURCES IN ENHANCEMENT PERFORMANCE ACADEMIC AND NON- ACADEMIC IN MADRASAH DINIYAH AR-ROFI'IYYAH CLOSE BY KRAKSAAN PROBOLINGGO - Maulidah, Hasanah Faiqoh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Public Relations as "Development Generator", Public Relations as development "Tools Of Promotion", Public Relations as "Absorbing and Conveying Community Aspirations", Public Relations as "Push and Pull Community participation in development, Public Relations as a "System of Balancing Physical and Non-Physical Development". Public Relations is needed by almost all forms of organizations or institutions, both commercial and non-commercial, from industrial companies, professional organizations, educational institutions, socio-cultural organizations to Islamic boarding schools. Public relations management planning is an act of determining in advance what will be done, both determining goals, targets to be achieved in accordance with what is expected and programs to be implemented.Before planning, it will first analyze the existing conditions in the educational environment related to the need assessment Implementation of Public Relations Management in Improving Open House students at PP Nurul Jadid Paiton Implementation of public relations management is the most important part of managing public relations management so that it can produce the best.